Informal Institutions, Informal Mechanisms, and their Utility in the Promotion of Environmental Protection in Africa (Strathmore Law Journal, 2025)
In the twenty-first century, there have been numerous attempts by the state in different African countries to preserve the environment, including the enactment of environmental laws, policies and regulations that are in force to date. These laws, policies and regulations have been instrumental in preserving the natural environment for current and future generations, in the prevention of further environmental degradation and in maintaining a sustainable relationship between mankind and the natural environment. However, beyond the reach of the state and its interventions, lies the existence of informal institutions such as indigenous communities and religion which play a powerful role in maintaining the natural environment. This article will explore these informal institutions and extract important aspects of their operation that are useful in conservation of the environment. The methodology applied is desktop research relying on journal articles, books, working papers and reports. The article is structured to assess informal institutions and their importance in environmental conservation, aspects of informal institutions such as self-coordination, collective action, collective identity and graduated sanctions, the role of religion as well as the accommodation of religion and informal institutions in international law. The paper uses the Plastics Treaty 2024 to demonstrate how appreciation and integration of religious and customary norms would eventually contribute to better outcomes in the governance of plastic waste.